Panarchy: opportunities and challenges for ecosystem management. Issue 10 (1st October 2020) - Garmestani, Ahjond; Twidwell, Dirac; Angeler, David G; Sundstrom, Shana; Barichievy, Chris; Chaffin, Brian C; Eason, Tarsha; Graham, Nick; Granholm, Dean; Gunderson, Lance; Knutson, Melinda; Nash, Kirsty L; et al.
Abstract : Addressing unexpected events and uncertainty represents one of the grand challenges of the Anthropocene, yet ecosystem management is constrained by existing policy and laws that were not formulated to deal with today's accelerating rates of environmental change. In many cases, managing for simple regulatory standards has resulted in adverse outcomes, necessitating innovative approaches for dealing with complex social–ecological problems. We highlight a project in the US Great Plains where panarchy – a conceptual framework that emerged from resilience – was implemented at project onset to address the continued inability to halt large‐scale transition from grass‐to‐tree dominance in central North America. We review how panarchy was applied, the initial outcomes and evidence for policy reform, and the opportunities and challenges for which it could serve as a useful model to contrast with traditional ecosystem management approaches.